Strategi Mengatasi Toxic Relationship Pada Remaja Yang Berpacaran Di SMKN 7 Surakarta Kelas 11 - Muna Majidah; Anniez Rachmawati Musslifah (Pusat Riset dan Inovasi Nasional, 2023)
This activity aims to find out the forms of toxic relationships in dating, the factors that cause toxic relationships in dating and the impact of toxic relationships on adolescent victims of toxic relationships in re-establishing relationships with the opposite sex. This activity uses presentation and question and answer methods with the aim of exploring and examining the experiences of adolescents who have been in toxic relationships in dating. The results of this activity on adolescents who have experienced toxic relationships in dating show that first, the factors that cause toxic relationships in adolescents at Smkn 7 Surakarta Class 11, namely internal factors such as unstable emotional state, immature way of thinking and victims of dependence on their partners while external factors such as the influence of the social environment, jealousy, cheating and disobedience. Second, the impact experienced by students who have experienced toxic relationships in dating, when re-establishing relationships with the opposite sex is a psychological impact such as the emergence of fear and trauma to re-establish relationships with the opposite sex. However, during the question and answer session, there were informants who claimed to have difficulty getting to know new people and finally chose to return to their toxic past on the grounds that their past loved them more than new people.